AKTIFITAS ANTI BAKTERI SPESIES ASTERIAS FORBESII TERHADAP BEBERAPA JENIS BAKTERI PATOGEN - Siti Juariah; Dwi Suryanto; It Jamilah (Fakultas Perikanan dan Kelautan, Universitas Riau, 2014)
ABSTRACTTo avoid contamination of bacteria pathogens natural and safe antibacterial agent is needed. The alternative sources of antibacterial compound is derived from sea star. In this extraction study of sea star activity showed that activity of the methanol from extract of starfish have the highest inhibition against for several bacterial pathogens compared to that of ethyl acetate and n-hexane extract with inhibition zone of 9.5 mm, 8.5 mm, 10.0 mm, 11.0 mm in S. aureus, B. subtilis, P. auroginosa and E. coli respectively. It showed that of TLC preparatif triterpenoid was capable inhibition more in Gram negative bacteria (Asterias forbesii) has been caried out to obtain antibacterial compounds. To determine bioactive components in the extract of sea star chemical test has been conducted. Toxicity of secondary metabolites was determind using method of Brine Shrimp Lethality Test (BSLT). Assay of antibacterial activity of starfish extract was conducted against four pathogenic bacterial strains, two Gram-positive bacteria (Staphylococcus aureus and Bacillus subtilis), and two Gram-negative bacteria (Pseudomonas auroginosa and Escherichia coli). The result showed that the methanol extract contained alkaloid, terpenoids, saponins and flavonoids, while the extract of n-hexane and ethyl acetate only contain saponins and flavonoids. BSLT test showed that LC50 of extract of n-hexane, ethyl acetate and methanol were 1412,54 ppm, 13182,57 ppm and 63,10 ppm respectively. Antibacterial (E. coli and P. auroginosa) bacteria compared with Gram positive (S. aureus and B. subtilis) .Keywords: Asterias forbesii, Staphylococcus aureus, Bacillus subtilis, Pseudomonas auroginosa, Escherichia coli, antibacterial compound